Structural lightweight design and experimental validation for aerospace sealed cabin - Zhizhong, Cheng; Hongqing, Li; Zengcong, Li; Yan, Chen; Jie, Chang; Xiaoqi, Li (Frontiers in Mechanical Engineering, 2023)
Due to the high specific stiffness, high specific strength, good fatigue resistance and high structural reliability, the integrally stiffened shells are widely applied in the sealed cabins. In order to enhance the detection distance of the deep space and improve the payload detection capability, it is of great significance to carry out lightweight design for the integrally stiffened shells. However, it is challenging to perform optimization for the structures due to the strict loading conditions, complicated structures and short development cycles. In this work, a novel layout design framework for the integrally stiffened shells under complex loading conditions is proposed. The topology optimization method is employed to obtain an innovative layout design of the integrally stiffened shells firstly, and then the mesh-mapping technique is utilized to assist the reconstruction and modeling process of the optimization result. Compared with the traditional design of orthogonal stiffeners, the weight of the optimized configuration of the integrally stiffened shell reduces by 17.1%, demonstrating excellent lightweight design effects. Moreover, a sealed cabin is constructed based on the optimization and numerical analysis result by taking the manufacturing requirement into consideration. With the purpose of assessing the bearing ability of the welded seam and evaluating the airtight performance of the sealed cabin, experimental validations of the hydrostatic test and airtight test are carried out, and the experimental results validate the applicability and effectiveness of the proposed framework.